Efficiency of Digital Storytelling in Learning Language (Eurasian Journal of Learning and Academic Teaching, 2023)
Technology has already become a crucial part of our lives, so hardly can we see any field that is not taking advantage of it. It has not been a long time ago when technology has been introduced in education. People started acquiring knowledge much faster and better thanks to new devices, and especially Internet. Through this many new techniques and approaches are created, and one of the is “Digital storytelling” which is a great help for learning languages more efficiently, and it also boosts creativity